The Role of English Language in Nigerian Development - Mishina, Ushuple Lucy; Iskandar, Iskandar (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The language policy in Nigeria granted the English language the status of being the sole official language, and the language of instruction in the country. This approach influenced the educated people’s competence, and subsequently, attitudes towards others within their locality and global arena. The study aims to investigate the role of the English Language in Nigerian Development. This paper argues that English as the Nigerian official language is well accepted due to the multi-lingual state of Nigeria. The study observes that English language is a political and social element in the process of building, unification, and maintaining the Nigerian state and as an essential element of national development. This study contributes to the understanding of multi-lingual nations and supports the research literature which shows that English language plays a significant role in unifying multilingual Nigeria.